Evaluation of indocyanine-mediated photodynamic therapy cytotoxicity on human osteoblast-like cells: an in vitro study - Shabnam Aghayan; Asma Yazdanfar; Ehsan Seyedjafari; Mohammad Noroozian; Roxana Ioana Bordea; Nasim Chiniforush (Folia Medica, 2022)
Introduction: Antimicrobial photodynamic therapy (aPDT) is an adjunctive non-invasive procedure for the management of periodontal tissue infection and deep periodontal pocket decontamination. However, the effects of this procedure on periodontal cells like osteoblasts that play a role in periodontal tissue repair and regeneration is not yet clear.Aim: This study aimed to investigate aPDT based on indocyanine green (ICG) on MG-63 osteoblast-like cells in vitro.Materials and methods: MG-63 cells were treated in 9 different groups: 1) Control (untreated cells), 2) ICG alone at a concentration of 1000 µg/mL, 3) ICG alone at a concentration of 2000 µg/mL, 4) diode laser irradiation alone for 30 s, 5) laser irradiation for 30 s combined with ICG with a concentration of 1000 µg/mL, 6) laser irradiation for 30 s combined with ICG at a concentration of 2000 µg/ mL, 7) laser irradiation alone for 60 s, 8) laser irradiation for 60 s combined with ICG at a concentration of 1000 µg/mL, and 9) laser irradiation for 60 s combined with ICG at a concentration of 2000 µg/mL. Cell viability was assessed by MTT assay in different groups.Results: In groups that were treated with 2000 µg/mL of ICG or diode laser irradiation at fluency of 39 J/cm2 for 60 s alone or in combination during ICG-aPDT, osteoblast-like cells viability decreased, remarkably.Conclusions: IGC-mediated aPDT with 1000 µg/mL of ICG combined with diode laser irradiation at fluency of 39 J/cm2 for 30 s is safe for MG-63 human osteoblast-like cells; however, higher concentration of ICG or laser irradiation time will increase cells death. There is still a need for more in vivo studies.